POLITENESS AND IMPOLITENESS STRATEGIES OF LECTURER AND STUDENTS IN ENGLISH CLASSROOM INTERACTION - SENNYA . NURDITASARI; Masitowarni . Siregar; Winda Setiasari . (Universitas Negeri Medan, 2023)
This study was discussed about the reasons of politeness and impoliteness strategies used by lecturer and students in English education classroom interaction based on Brown & Levinson and Culpeper theory. This article was aimed to found the reasons why lecturer and students used politeness and impoliteness strategies in classroom interaction. This article used two theories in doing the analysis namely Brown & Levinson theory for the reason of using politeness strategies and Culpeper theory for the reason of using impoliteness strategies. This article applied descriptive qualitative method. The data of this research were the lecturer and students’ utterances in English education classroom interaction which taken from audio transcript and the result of interview the lecturer and representative of students. The results have revealed that there are five reasons why the lecturer used politeness strategies, namely speaker wants the hearer interpret what she means; to give the hearer chance to be perceived as caring person; to increase familiarity and friendship;to respect the hearer and to make the hearer understand directly, one reason why the students used politeness strategies namely to satisfy the hearer’s negative face and one reason why the students used impoliteness strategies namely to express negative feelings.